The interplay between extracellular NAMPT and inflammatory cytokines in preeclampsia - Nunes, Priscila Rezeck [UNESP]; Pereira, Daniela Alves; Passeti, Luis Fernando Pereira [UNESP]; Coura, Lídia Lana Ferreira; Gomes, Karina Braga; Sandrim, Valeria Cristina [UNESP]; Luizon, Marcelo Rizzatti [UNESP] (Elsevier, 2024)
Preeclampsia (PE) is the major cause of maternal-fetal mortality and morbidity. Its pathophysiology is not elucidated, but there is evidence for the role of visfatin/nicotinamide phosphoribosyl transferase (NAMPT), mainly due to its relation to endothelial dysfunction, a hallmark of PE. However, there is heterogeneous data regarding visfatin/NAMPT in healthy pregnancy (HP) and PE. Therefore, we performed a search on MEDLINE/PubMed using the terms “visfatin and preeclampsia” and “NAMPT and preeclampsia, and we selected 23 original articles: 12 articles reported increased levels in PE compared to HP, only four articles showed lower levels and eight articles did not find differences regarding visfatin/NAMPT in the groups studied. It is widely acknowledged that levels detected in plasma, serum, or placenta can be influenced by the size of the population and sample analyzed, as well as genetic factors. We further discussed the correlations of visfatin/NAMPT with clinical biomarkers in PE and inflammatory pathways. Considering the common inflammatory mechanisms between PE and visfatin/NAMPT, few studies have recently performed serum or plasma dosages. In conclusion, further studies are needed to highlight the potential role of visfatin/NAMPT in the pathophysiology of PE. This will provide comparative evidence to establish it as a biomarker for disease outcomes and treatment.
Keywords: Cytokines; Endothelial dysfunction; Extracellular nicotinamide phosphoribosyltransferase (eNAMPT); Inflammation; Nicotinamide phosphoribosyl transferase; Toll-like receptor; Visfatin/NAMPT